2016
DOI: 10.1111/ases.12284
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously ruptured hepatic cyst treated with laparoscopic deroofing and cystobiliary communication closure: A case report

Abstract: The rupture of a nonparasitic hepatic cyst with biliary communication is rare. We report the case of a patient with a hepatic cyst with biliary communication that spontaneously ruptured and was successfully treated by laparoscopic deroofing and closure of the communication. A 61-year-old woman presented at our hospital with a chief complaint of right upper abdominal pain. Enhanced abdominal CT showed a collapsed hepatic cyst and fluid collection. Drip infusion CT cholangiography showed contrast medium pooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
(9 reference statements)
0
17
0
Order By: Relevance
“…This approach might not be suitable for all cases, especially for unstable patients (bleeding or septic), cysts located in the upper and posterior segments of the liver (difficult access) and those with a biliary communication. There are only three other cases reported using laparoscopic surgery as an emergency procedure [1, 3, 9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach might not be suitable for all cases, especially for unstable patients (bleeding or septic), cysts located in the upper and posterior segments of the liver (difficult access) and those with a biliary communication. There are only three other cases reported using laparoscopic surgery as an emergency procedure [1, 3, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Usually they are asymptomatic and can be managed conservatively, but about 5% of NHCs become large and symptomatic, causing abdominal pain, bloating, nausea, vomiting and dyspnoea. Those becoming symptomatic may require treatment and various procedures have been proposed such as aspiration, sclerotherapy, deroofing, enucleation or hepatectomy [2, 3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review by Imaoka et al identified 18 relevant publications (29 cases) on non-parasitic hepatic cyst ruptures between 1959 and 2015 8. We further identified four publications,9–12 making a total of 34 cases (Imaoka included). Eleven of these resulted in haemoperitoneum, but only two were associated with long-term anticoagulation 10 13.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic cyst combined with bile duct infection was also the most common cause of rupture. 5 Biliary communication, repeated infection of bile in the cyst fluid could easily cause damage to the cyst wall. We also confirmed this phenomenon in this case.…”
mentioning
confidence: 99%